Evaluating the effectiveness of social media enabled collaborative learning environments (SMECLEs). (10th June 2016) - Doyle, Cathal; Neville, Karen; Sammon, Dave
Abstract: Collaborative technologies such as Group Decision Support Systems (GDSS) were proclaimed to be able to impact the learning environments of educational institutions twenty years ago. It was understood that these technologies were effective at transforming learning environments from a traditional approach to a collaborative one, where the learner is part of the learning process, but little has actually changed in this time. New generations of these collaborative technologies often emerge, and the platforms of social media are one such technology. In a similar fashion to previous collaborative technologies, social media have been proclaimed as impacting the learning environments of educational institutions through better communication and collaboration, in new and exciting ways. However, there is a lack of understanding on whether the platforms of social media are effective at enabling collaborative learning. This study helps improve this understanding by analysing two types of social media enabled collaborative learning environments (SMECLEs).